Bunyi Religius Bantul: Menelusuri Kebisingan Dari Masjid Sebagai Ruang Ibadah - Prawito, Edi; Nururi, Imam (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2024)
This research aims to investigate the impact of religious sounds in Bantul on the quality of daily life of local residents, especially in the context of noise originating from mosques as prayer spaces. Noise generated from prayer spaces which seem taboo in discussions in society has created new discussions. A qualitative approach was used in this research with data collection carried out by observation and interviews with several communities in Bantul. This research is to reveal the impact of religious sounds in Bantul worship spaces. The results of the research show that religious sounds in prayer rooms cause ongoing problems for the surrounding community related to excessive loudspeakers, such as disturbing individuals' privacy for resting, doing assignments and other activities that require peace. In conclusion, the impact of noise from the Worship Room reduces comfort and interferes with individual activities such as resting and studying. There needs to be stricter regulations regarding the use of loudspeakers and volume limits. Apart from that, the noise management strategy must involve various parties to evaluate the intensity and pattern of noise and provide education to the congregation and mosque administrators so that good communication can be created and does not harm any party.